Comparison of Outcome on Early and Late Initiation Of Operative Treatment in Children With Lateral Condyle Fracture of Humerus (Journal of Chittagong Medical College Teachers' Association, 2020)
Background: Lateral condyle fracture of humerus in children is the second most common fracture around elbow occurs less commonly than supracondylar fracture in the range of 15% to 20% that must be treated by operation. To find out the demographic variations, causes, functional movements and complications of late cases of lateral condyle fracture of humerus in children treated by open reduction and internal fixation and also comparison with early cases.Materials and methods: This prospective interventional study was carried out in the Department of Orthopaedic Surgery, Bangabandhu Sheikh Mujib Medical University and Chittagong Medical College Hospital for the duration of 03 years and 06 months. Total 24 patients of fracture lateral condyle of humerus in children age ranges from 02 to 14 years were selected but due to loss of follow up, 20 children were taken in account for the study. Total patients were divided into two groups- group I: early (Up to 4 weeks) and group II: late (5 to 12 weeks) according to time interval from injury to operative treatment.Results: In this study, Out of 20 patients, male (85%) were more than female (15%) left side involvement was 60% and right side was 40%. Among causes of injury, 55% was due to sports injury, 30% was fall from height and 15% from RTA. 35% initially treated by plaster cast, 60% by traditionally bone setter. 55% were misdiagnosed, complications were 10% in group I and 30% in group II. Outcome was satisfactory with 100% in group I and 70% in group II.+Conclusion: Outcome was better in early cases by operative treatment but late cases up to 12 weeks should be treated by operation.JCMCTA 2019 ; 30 (2) : 10-15